From Prehistory to History on the Ḫabur Plains: The Operation 1 Ceramic Periodization from Tell Leilan - Schwartz, Glenn Martin (1982)
Ph.D. Dissertation; Order No. DA8310520; cf. DissAbstr 43/12 (1983) 3955-A/3956-A.